Board gender diversity and dividend policy in Australian listed firms: the effect of ownership concentration - Gyapong, Ernest; Ahmed, Ammad; Ntim, Collins G; Nadeem, Muhammad (Asia Pacific journal of management, 2021)
We examine the association between board gender diversity and corporate dividend payout. Our results suggest that although board gender diversity impacts positively on dividend payments, this is only conspicuous in widely held firms. However, when ownership concentration is high, board gender diversity reduces dividend payments. We demonstrate that women directors have the greatest impact on dividend payments when there are three or more women on the board. Our results indicate that the financial crisis period was associated with high dividend payments; however, women directors restrained the payment of dividends during the crisis period. These results suggest that board gender diversity may be an effective CG mechanism for alleviating principal-agent conflicts but not principal-principal agency conflicts. Our results are robust to endogeneity, as well as alternative proxies and estimation techniques.